Efficiency measurement in healthcare: The foundations, variables, and models. A narrative literature review - Antony Andrews; Grigorios Emvalomatis (Economics: The Open-Access, Open-Assessment Journal, 2024)
Efficiency and productivity analysis have been critical in healthcare and economics literature. Despite the tremendous innovation in methodology and data availability, a comprehensive literature review on this topic has not been conducted recently. This article provides a three-part literature review of healthcare efficiency and productivity studies. It begins by reviewing the two primary empirical methods used in healthcare efficiency studies, emphasising the treatment of inefficiency persistence. Second, previous contributions to healthcare productivity research are discussed with a focus on methodology and findings. In the third section, various measures of outputs, inputs, and prices in health literature are explored to determine the extent of consensus in the literature. On the methodological front, the literature review shows that while the Data Envelopment Analysis and the Stochastic Frontier Analysis have been used extensively in healthcare productivity and efficiency studies, their application in the context of longitudinal data is limited. Further, no study currently undertakes to measure the TFP changes and its components that use both primal and dual approaches. There is also a considerable variation in the use of inputs, outputs, and price variables, suggesting that the use of variables in healthcare productivity and efficiency literature rests on the balance between data availability and the research scope.
Keywords: 330; stochastic frontier; hospital efficiency; dea